Do individuals have consistent risk preferences across domains? Evidence from the Japanese insurance market - Yoichiro Fujii; Noriko Inakura (Journal of Applied Economics, 2022)
The risk attitude plays an important role in analyzing decision making under uncertainty. It is essential to confirm whether the risk aversion parameter in a certain situation, called "domain," can be applied to other situations. Using a dataset on hospitalization insurance policies in Japan, this study tests whether individuals' risk preferences remain consistent across domains. Based on the assumption of expected utility maximizer, we derive a plausible distribution of the degree of risk aversion. We find that degree of risk aversion is consistent between hospitalization benefits and additional insurance for specific diseases. Contrarily, the degree of risk aversion from hospitalization benefits has a negative relationship with that based on a survey question on the self-assessment of general preferences. This result indicates that the imputation of risk aversion from the literature would distort research results markedly if characteristics of the domains targeted by both previous research and this study differ.
Keywords: 330; domain; insurance choices; internal validity and external validity; Risk attitude